Cultivation of the edible mushrooms pleurotus ostreatus and its nutritional composition on spent ground coffee - Nieto Juárez, Jessica Ivana (2021)
The Cultivation of the edible mushrooms Pleurotus ostreatus on spent ground coffee was studied with the purpose of evaluating its potential as a treatment method for the valorization of this coffee waste. Its nutritional composition of macro and micronutrients was also evaluated as a quality control, to verify that the food product (oyster mushrooms) is of high nutritional value and free of toxic substances for human consumption. The influence of the amount of mycelial seed on the efficiency of production of the edible mushrooms was investigated, obtaining an optimal quantity between 10 and 20 % (g seed /100 g wet substrate) with a biological efficiency of roughly 60 %. The protein value was of 47.3 % on dry sample, with a high-water content (~ 90 %) and a low content in carbohydrates (5.4 %) and fats (0.2 %) in fresh sample. The analysis of microelements in the oyster mushrooms shows that potassium is the most predominant element, followed by magnesium, calcium, and sodium and in trace elements have silicon, iron, copper, and zinc in dry sample. The caffeine content was less than 60 µg/g in dry sample. Therefore, the results indicate that spent ground coffee is a potential waste for the cultivation of oyster mushrooms (Pleurotus ostreatus), generating a highly protein and healthy food, which could be included in the daily diet, and thus contribute to improve the health of people, nutrition and control some diseases.